2008
DOI: 10.1590/s1517-83822008000100021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cinnamomum zeylanicum blume essential oil on the rowth and morphogenesis of some potentially pathogenic Aspergillus species

Abstract: Cinnamomum zeylanicum Blume is known for a wide range of medicinal properties. This study aimed to assess the interference of C. zeylanicum essential oil on the growth and morphogenesis of some potentially pathogenic Aspergillus species. The essential oil presented strong antifungal effect causing the growth inhibition of the assayed strains and development of large growth inhibition zones. MIC50 and MIC90 values were 40 and 80 µL/mL, respectively. 80, 40 and 20 µL/mL of the oil strongly inhibited the radial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 42 publications
(59 reference statements)
4
23
0
5
Order By: Relevance
“…These results are consistent with studies of the effect of cinnamon oil on the growth of Aspergillus ochraceus (6,7). High concentrations of cinnamon seem to inhibit the development of asexual spores and cause signifi cant morphological changes in the mycelium of the Aspergillus genera (6).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are consistent with studies of the effect of cinnamon oil on the growth of Aspergillus ochraceus (6,7). High concentrations of cinnamon seem to inhibit the development of asexual spores and cause signifi cant morphological changes in the mycelium of the Aspergillus genera (6).…”
Section: Discussionsupporting
confidence: 87%
“…Many essential oils and their ingredients possess antibacterial, antifungal, and antiviral properties (5)(6)(7)(8)(9)(10)(11)(12)(13). These include cassia, cinnamon, clove, garlic, sage, oregano, pimento, thyme, rosemary, scutellaria, and other (14).…”
mentioning
confidence: 99%
“…The mechanism of antioxidantive action regarding the inhibition of mycelial growth of toxigenic fungi is not clear. Many studies have described antioxidative effects of antifungal compounds, their relation to protoplasmic poisoning, disruption of microbial cell wall, and precipitation of cell proteins (10,15). The activity of these compounds has been attributed to the presence of an aromatic nucleus and an OH group which are known to form hydrogen bonds within active sites of enzymes (10,16,17).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its culinary uses, cinnamon has been used in traditional herbal medicine to treat different health conditions (Gruenwald et al, 2010). Some studies showed that cinnamon extracts and its constituents also effective in the treatment of cancer (Nishida et al, 2003), insecticidal (Yang et al 2005), hypotensive (Preuss et al, 2006), antioxidant and antimutagenic activities (Jayaprakasha et al, 2007), cholesterol-lowering effects (Subash Babu et al, 2007), antimicrobial action (Carmo et al, 2008) and anti-inflammatory effect (Tung et al, 2008). The liver is the largest internal organ in the body and played a very important role in the detoxification of harmful and toxic substances.…”
Section: Introductionmentioning
confidence: 99%